2007
DOI: 10.1017/s1755691007078462
|View full text |Cite|
|
Sign up to set email alerts
|

A reappraisal of feeding current systems inferred for spire-bearing brachiopods

Abstract: International audienceSpire-bearing brachiopods formally comprise four different rhynchonelliform orders. A calcified spiral brachidium (presumably supporting a spirolophe when alive) and variable median fold and sulcus (probably aiding separation of incurrent from excurrent flows) are peculiar characteristics they all share. Inferences regarding feeding current systems for these extinct taxa have long remained controversial. Two rival models (the Williams–Ager model and the Rudwick–Vogel model) have been deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 41 publications
2
24
0
Order By: Relevance
“…The flow tests demonstrated that the continuous stream of the surrounding water generated a medial inflow current into the gaping shell models and wide zones of outflows along the lateral sides. Besides proving the previous model (Manceñido and Gourvennec, 2008), Shiino's (2010) experiments brought forward an important new element as they revealed the presence of an invariable spiral flow system inside the spiriferide models. This gyrating flow closely followed the laterally oriented spiral brachidium of the model specimens.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…The flow tests demonstrated that the continuous stream of the surrounding water generated a medial inflow current into the gaping shell models and wide zones of outflows along the lateral sides. Besides proving the previous model (Manceñido and Gourvennec, 2008), Shiino's (2010) experiments brought forward an important new element as they revealed the presence of an invariable spiral flow system inside the spiriferide models. This gyrating flow closely followed the laterally oriented spiral brachidium of the model specimens.…”
Section: Discussionmentioning
confidence: 68%
“…The selective extinction of spiriferinids, together with the other spire-bearing group, the athyridids, is best explained by their internal features: the spiral brachidia and the firmly attached lophophore. Manceñido and Gourvennec (2008) gave an exhaustive review and evaluation of the decades-long research and debates by a great number of authors on the feeding current system of spire-bearing brachiopods, including the results of both early flume experiments and observations on fossil interactions with epi-and endobionts. Their tentative conclusion is that the extinct spiriferids and spiriferinids used their laterally tapering spiralia and the attached spirolophs as a kind of plankton net and took advantage of a passive flow system with a median inhalant and two lateral exhalant sectors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results indicate that a deeper sulcus could generate a higher pressure difference, thereby creating a more vigorous inflow through the sulcus gape and resulting in stronger spiral flows with a higher number of revolutions (Shiino and Kuwazuru, 2010b). Using a different line of reasoning, a deeper sulcus may result in a more vigorous inflow because the water flowing into the shell through the sulcus gape would be available for the basal spire to capture food particles (Manceñ ido and Gourvennec, 2008).…”
Section: Passive Feeding Flow Of Paraspirifermentioning
confidence: 97%
“…This has also been suggested for extinct productids (Shiino andSuzuki, 2007, 2010). An allometric relationship along ontogeny has been described, relating both the progressive broadening of the sulcus and concomitant widening distance between the bases of each spiralium (Manceñ ido and Gourvennec, 2008). To understand the differences due to ontogeny more clearly, the relationship between allometric scaling and functional performance should be examined in the future.…”
Section: Future Perspectives On Theoretical Approaches To the Optimismentioning
confidence: 99%